2018
DOI: 10.3389/fimmu.2018.01904
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of CD8+ Tissue Resident Memory T (TRM) Cells in Antitumor Immunity: A Unique Functional Contribution of the CD103 Integrin

Abstract: Cancer immunotherapy is aimed at stimulating tumor-specific cytotoxic T lymphocytes and their subsequent trafficking so that they may reach, and persist in, the tumor microenvironment, recognizing and eliminating malignant target cells. Thus, characterization of the phenotype and effector functions of CD8+ T lymphocytes infiltrating human solid tumors is essential for better understanding and manipulating the local antitumor immune response, and for defining their contribution to the success of current cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(129 citation statements)
references
References 90 publications
(145 reference statements)
3
123
0
Order By: Relevance
“…Of note, Itgb7 was co-expressed in EM-like cells with the integrin subunit α4 (Itga4) but not with Itgae (CD103), with which ITGB7 dimerizes in tissue-resident T cells. 68 Instead, the α4β7 integrin has been previously shown to mediate lymphocyte migration to gut-associated lymphoid tissue and might have a different function in the context of tumors. 69 Multiple studies have established that PD-1 blockade increases T cell infiltrations in tumors leading to improved anti-tumor control.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, Itgb7 was co-expressed in EM-like cells with the integrin subunit α4 (Itga4) but not with Itgae (CD103), with which ITGB7 dimerizes in tissue-resident T cells. 68 Instead, the α4β7 integrin has been previously shown to mediate lymphocyte migration to gut-associated lymphoid tissue and might have a different function in the context of tumors. 69 Multiple studies have established that PD-1 blockade increases T cell infiltrations in tumors leading to improved anti-tumor control.…”
Section: Discussionmentioning
confidence: 99%
“…At the protein level however, ITGB7 was expressed only by a subset of EM-like cells (Figure 2 C). Of note, Itgb7 was co-expressed in EM-like cells with the integrin subunit a4 (Itga4) but not with Itgae (CD103), with which ITGB7 dimerizes in tissue-resident T cells (Corgnac et al, 2018). Instead, the a4b7 integrin has been previously shown to mediate lymphocyte migration to gut-associated lymphoid tissue and might have a different function in the context of tumors (Denucci, Mitchell and Shimizu, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…64 PD-1-mediated expansion of T cells appear to act on CXCR5 + /TIM3 À T cells, as well as tissue and tumorresident memory T cells. 36,66 However, it does not appear to reverse exhaustion in majority of T cells. 15,67 It was recently demonstrated that a proportion of supposedly "exhausted" tumor-infiltrating T cells that express TCF1 (see below) preferentially respond to anti-PD1 treatment and could transform into self-renewing memory cells.…”
Section: Immune Checkpoint Blockadementioning
confidence: 99%
“…Tissue resident memory T cells (T RM ) resemble T EM in that they home to nonlymphoid tissue, but T RM express CD103 and CD69, do not recirculate, and are self‐renewing in situ . The degree of infiltration of solid tumors by T RM may be a useful indicator of anti‐cancer responses, including the success of immune checkpoint inhibition . T RM appear to possess direct cytotoxicity, which is dependent on CD103 interactions .…”
Section: Subsets Of Memory Cellsmentioning
confidence: 99%